Gel-Trapped Lymphorganogenic Chemokines Trigger Artificial Tertiary Lymphoid Organs and Mount Adaptive Immune Responses In Vivo - Kobayashi, Yuka; Watanabe, Takeshi (Frontiers in Immunology, 2016)
We previously generated artificial lymph node-like tertiary lymphoid organs (artTLOs) in mice using lymphotoxin α-expressing stromal cells. Here, we show the construction of transplantable and functional artTLOs by applying soluble factors trapped in slow-releasing gels in the absence of lymphoid tissue organizer stromal cells. The resultant artTLOs were easily removable, transplantable, and were capable of attracting memory B and T cells. Importantly, artTLOs induced a powerful antigen-specific secondary immune response, which was particularly pronounced in immune-compromised hosts. Synthesis of functionally stable immune tissues/organs like those described here may be a first step to eventually develop immune system-based therapeutics. Although much needs to be learned from the precise mechanisms of action, they may offer ways in the future to reestablish immune functions to overcome hitherto untreatable diseases, including severe infection, cancer, autoimmune diseases, and various forms of immune deficiencies, including immune-senescence during aging.